Effect of edaphic and foliar management of manganese on the yield of the criolla colombia cultivar (2011)
This research was conducted in the district of El Rosal (Cundinamarca) in a Typic Hapludand soil and sought to evaluate the effect of foliar and soil applications of different doses of manganese (Mn) (0, 1, 2 and 3 kg ha -1) on the potential yield of the Criolla Colombia cultivar. Sulphate Mn granules (Microman ®) and chelated Mn (MF-Mn®) were used as sources. We used a split-plot, randomized complete block design with four replications per treatment. The variables studied were: weight and number of tubers per category. The results show that the application of both soil and foliar Mn exerts a positive response in the criolla potato, with increases of 52% in commercial yield and more than 100% in first category yield with respect to traditional fertilization. The optimal dose is between 1.5 to 2.0 kg ha-1 for both soil and foliar Mn, with an economic optimum between 0.8 to 1 kg ha-1 Mn, edaphically applied. The results showed no differences between the techniques of foliar and soil application for yield potential, but did for number of tubers.